Leishmania development in sand flies: parasite-vector interactions overview - Dostálová, Anna; Volf, Petr (Parasites & vectors, 2012)
Leishmaniases are vector-borne parasitic diseases with 0.9 - 1.4 million new human cases each year worldwide. In the vectorial part of the life-cycle, Leishmania development is confined to the digestive tract. During the first few days after blood feeding, natural barriers to Leishmania development include secreted proteolytic enzymes, the peritrophic matrix surrounding the ingested blood meal and sand fly immune reactions. As the blood digestion proceeds, parasites need to bind to the midgut epithelium to avoid being excreted with the blood remnant. This binding is strictly stage-dependent as it is a property of nectomonad and leptomonad forms only. While the attachment in specific vectors (P. papatasi, P. duboscqi and P. sergenti) involves lipophosphoglycan (LPG), this Leishmania molecule is not required for parasite attachment in other sand fly species experimentally permissive for various Leishmania. During late-stage infections, large numbers of parasites accumulate in the anterior midgut and produce filamentous proteophosphoglycan creating a gel-like plug physically obstructing the gut. The parasites attached to the stomodeal valve cause damage to the chitin lining and epithelial cells of the valve, interfering with its function and facilitating reflux of parasites from the midgut. Transformation to metacyclic stages highly infective for the vertebrate host is the other prerequisite for effective transmission. Here, we review the current state of knowledge of molecular interactions occurring in all these distinct phases of parasite colonization of the sand fly gut, highlighting recent discoveries in the field.
Keywords: gastrointestinální trakt; Psychodidae; Gastrointestinal Tract; Insect Vectors; zvířata; hmyz - vektory; Leishmania; Animals